2006
DOI: 10.1021/jm061063g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Azaspiracid-1, A Potent Cytotoxic Agent, on Primary Neuronal Cultures. A Structure−Activity Relationship Study

Abstract: Azaspiracids (AZAs) are marine phycotoxins with an unknown mechanism of action, implicated in human intoxications. We investigated the effect of azaspiracid-1 (AZA-1) on the cytosolic calcium concentration ([Ca2+]c), intracellular pH (pHi), and neuron viability in neuronal cultures. AZA-1 increased [Ca2+]c and decreased neuronal viability. The effects of several fragments of the AZA-1 molecule (13 different chemical structures) were examined. The ent-ABCD-azaspiracid-1 (2) showed similar potency to AZA-1 (1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 31 publications
3
76
1
2
Order By: Relevance
“…We have recently shown that AZA-1 is a potent neurotoxic agent in primary neuronal cultures showing an effect several orders of magnitude higher than the cytotoxic effects previously described in different cell lines [14,15]. The cytotoxic action of AZA-1 in neurons was independent of an alteration on the cytosolic calcium concentration or on F-actin cytoskeleton disruption and it needed the whole molecular structure of the toxin [15]. In view of the high cytotoxic effect of AZA-1 in neuronal cultures we conducted a pharmacological and molecular approach to explore several potential pharmacological targets of azaspiracids in nervous tissue.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We have recently shown that AZA-1 is a potent neurotoxic agent in primary neuronal cultures showing an effect several orders of magnitude higher than the cytotoxic effects previously described in different cell lines [14,15]. The cytotoxic action of AZA-1 in neurons was independent of an alteration on the cytosolic calcium concentration or on F-actin cytoskeleton disruption and it needed the whole molecular structure of the toxin [15]. In view of the high cytotoxic effect of AZA-1 in neuronal cultures we conducted a pharmacological and molecular approach to explore several potential pharmacological targets of azaspiracids in nervous tissue.…”
Section: Introductionmentioning
confidence: 78%
“…So far, there is no information about the mechanism of action of the AZAs or of their specific cellular targets. We have recently shown that AZA-1 is a potent neurotoxic agent in primary neuronal cultures showing an effect several orders of magnitude higher than the cytotoxic effects previously described in different cell lines [14,15]. The cytotoxic action of AZA-1 in neurons was independent of an alteration on the cytosolic calcium concentration or on F-actin cytoskeleton disruption and it needed the whole molecular structure of the toxin [15].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A. obesum and A. caudatum are the only members of the genus Azadinium established in culture for which no AZA has been detected. While the AZAs produced by A. spinosum have been shown empirically to be toxic (Ito et al 2002, Román et al 2002, Colman et al 2005, Alfonso et al 2006, Kulagina et al 2006, Vale et al 2007, research is pending for the new AZAs.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments with mammalian cell lines showed alterations in the cytoskeletal structure (Roman et al, 2002;twiner et al, 2005;Ronzitti et al, 2007;Vilarino et al, 2006;Paredes et al, 2011). AZP toxins increase intracellular Ca 2+ concentrations and cAMP levels in human lymphocytes and primary cultures of cerebellar granule cells (Roman et al, 2002;Vale et al, 2007b). In addition these toxins induce increased phosphorylated Junkinases in primary cultured neurons (Vale et al, 2007a).…”
Section: Mode Of Actionmentioning
confidence: 99%